21. EVALUATION OF GROSS MOTOR FUNCTIONAL ACTIVITIES GMFM-88 IN A CASE OF A CHILD WITH DEVELOPMENTAL DELAY (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of applying the GMFM scale in assessing and setting appropriate goals in the rehabilitation of a child with cerebral palsy.Subjects and Methods: A case study was conducted on a child diagnosed with cerebral palsy, assessing the severity and setting treatment goals over an 8-week period.Results: After 8 weeks of treatment, assessments using the GMFM scale showed improvements in domains A, B, C, and D with scores of 51, 12, 30, and 8, respectively. Domain E could not be evaluated as the patient discontinued treatment.
Keywords: GMFM scale, cerebral palsy, rehabilitation.